Tanggung Jawab Hukum Kontraktor Dalam Proyek Mangkrak di Maluku Barat Daya - Leonardo Karel Hurulean; Ali Maskur (International Forum of Researchers and Lecturers, 2024)
A complex construction project entails the legal liability of the contractor and the process of its completion. The project of building a 2 tonne/day small-scale solar ice factory is in disarray due to a lack of funding in the completion process. The decline in local tax revenues and the loss of potential jobs for local communities, slumped local economic growth and the well-being of communities. The crumbling small-scale solar ice plant also hampers the potential for infrastructure development in Southwest Maluku district. The purpose of this research is to investigate the legal responsibility of contractors in corrupt construction projects as well as to identify the legal settlement process against contractors In the case of the Mangkrak project in the Fisheries Department of Maluku District West South. Qualitative research using empirical jurisprudence methods to obtain data on legal settlement processes in cases of crashed projects. The results of the research show that contractors have a legal responsibility to complete the project in accordance with the agreed contract. The process of legal settlement by means of negotiation between the parties concerned, arbitration and legal claims. The importance of monitoring the implementation of the project in order to avoid future projectcrashes